Transparency‐tunable and moderate‐temperature healable thermoplastic polyurethane elastomer based on bisphenol A chain‐extender. Issue 6 (18th August 2020) - Xiang, Chuanxi; Chen, Hongxiang; Wang, Wanwan; Dai, Qiaoli; Liu, Zhiqiang; Yang, Bing; Zhou, Yu; Zhou, Yang
Abstract: Transparent self‐healing polymers have a promising future, but the research on the relationship among transparency, self‐healing, and structure is still challenging. The thermoplastic polyurethane elastomers containing aryl carbamate were prepared by the reaction of isocyanate‐terminated prepolymer and chain‐extender bisphenol A (BPA). On the one hand, the thermoplastic polyurethane elastomer could heal at a relatively low temperature due to the exchange of aryl carbamate, and exhibits 83% of healing efficiency at 90°C for 2 h. On the other hand, two methyl groups of BPA hinder the crystallization of hard segments in polyurethane, so the domain of hard segments is amorphous, while the microcrystals of soft segments dispersed in the polyurethane are affected by the content of hard segments, therefore, the transparency of polyurethane can be tailored by the content of hard segments. It provides a simple design and a feasible preparation method for transparent self‐healing polymer. Abstract : The study on the relationship among transparency, self‐healing and structure of polymers is still challenging. The exchange of aryl carbamates is more easily achieved because of relatively lower nucleophilicity of phenolic hydroxyl compared with alcoholic hydroxyl. Bisphenol A was incorporated into polyurethane, and the thermal healing temperature decreased. In addition, the two methyl groups of bisphenol A hindered the crystallization of hard segments, which offered a possibility to tailor the transparency of polyurethane.